PENDAMPINGAN LITERASI PEACEBUILDING DENGAN PENDEKATAN DAKWAH PERSUASIF PASCA KONFLIK SUKU DAYAK MADURA PADA KOMUNITAS MASYARAKAT PENGUNGSI SUKU MADURA - Munir, Miftahul; Azis, Abd.; Rosi, Bahrur (Ulumuna: Jurnal Studi Keilsman, 2022)
Peace building literacy assistance to refugees of the Madurese conflict in Pamekasan Regency is an urgent step as a preventive measure for subsequent conflicts that continue to haunt Madurese refugees in Pamekasan. The refugees must obtain comprehensive knowledge about the diversity of the Republic of Indonesia through an approach that suits their characteristics, namely a persuasive da'wah approach as an effort to operationalize friendly Islamic teachings in a concrete form. This is because the refugees still have a high desire to return to Kalimantan someday. In fact, many of their family members had already returned to the island of Borneo to seek fortune as they had before the bloody events several decades ago which became a black record for the Indonesian nation. This mentoring activity uses a Word of Mouth approach, namely conveying messages by word of mouth as an individual approach and through "koloman" or halaqoh-halaqoh, namely group activities which have become a habit for Madurese people. Keywords: Peacebuilding Literacy, Word of Mouth dan â€œKolomanâ€